Rice SPX-Major Facility Superfamily3, a Vacuolar Phosphate Efflux Transporter, Is Involved in Maintaining Phosphate Homeostasis in Rice. Issue 4 (30th September 2015) - Wang, Chuang; Yue, Wenhao; Ying, Yinghui; Wang, Shoudong; Secco, David; Liu, Yu; Whelan, James; Tyerman, Stephen D.; Shou, Huixia
Abstract : A transporter orthologous to a yeast vacuole phosphate transporter mediates phosphate efflux from the vacuole into the cytosol. Abstract: To maintain a stable cytosol phosphate (Pi ) concentration, plant cells store Pi in their vacuoles. When the Pi concentration in the cytosol decreases, Pi is exported from the vacuole into the cytosol. This export is mediated by Pi transporters on the tonoplast. In this study, we demonstrate that SYG1, PHO81, and XPR1 (SPX)-Major Facility Superfamily (MFS) proteins have a similar structure with yeast ( Saccharomyces cerevisiae ) low-affinity Pi transporters Phosphatase87 (PHO87), PHO90, and PHO91. OsSPX-MFS1, OsSPX-MFS2, and OsSPX-MFS3 all localized on the tonoplast of rice ( Oryza sativa ) protoplasts, even in the absence of the SPX domain. At high external Pi concentration, OsSPX-MFS3 could partially complement the yeast mutant strain EY917 under pH 5.5, which lacks all five Pi transporters present in yeast. In oocytes, OsSPX-MFS3 was shown to facilitate Pi influx or efflux depending on the external pH and Pi concentrations. In contrast to tonoplast localization in plants cells, OsSPX-MFS3 was localized to the plasma membrane when expressed in both yeast and oocytes. Overexpression of OsSPX-MFS3 results in decreased Pi concentration in the vacuole of rice tissues. We conclude that OsSPX-MFS3 is a low-affinity Pi transporter that mediates Pi efflux from the vacuole into cytosol and is coupled to proton movement.